Book Review: Eran Feitelson and Erik T. Verhoef (eds) Transport and Environment. In Search of Sustainable Solutions - Givoni, Moshe (European Journal of Transport and Infrastructure Research, 2002)
Transport and Environment is a collection of papers that aim at “bringing together contributions from various disciplines to the study of the broad field of ‘Transport and Environment’” (p: xiii). The focus of the book is “the search for practical solutions that can advance the sustainability notions” (p: 5), and the emphasis of the book is on “technology measures and spatial (or planning) policies” (p: 9). All this sets the context in which this book should be judged against.